Research trends in mathematics education: A quantitative content analysis of major journals 2017-2021 - Katibe Gizem Yığ (Journal of Pedagogical Research, 2022)
This research aims to uncover current trends and key issues by examining the research in mathematics education during the period 2017-2021. For this purpose, five major peer reviewed academic journals indexed by the Social Sciences Citation Index (SSCI) in Web of Science (WoS) have been examined in detail: "Educational Studies in Mathematics", "Journal for Research in Mathematics Education", "International Journal of Science and Mathematics Education", "Journal of Mathematics Teacher Education" and "Mathematical Thinking and Learning". A total of 881 articles were examined within the scope of the research. Bibliometric analysis and social network analysis (SNA) were used in the analysis procedure. Occurrence/co-occurrence combinations of author keywords and concepts in abstract sections have been created in order to perform the relevant analyses. These undirected network combinations were then analysed through NodeXL and VOSviewer software. The results were visualized and interpreted according to link strength, relevance scores, betweenness and degree centrality metrics. According to the common findings from both analysis approaches, in the 2017-2021 period, the most focused and prominent research issues in the field of mathematics education have revealed different main sets: studies related to mathematics teachers and teacher education (and especially teacher noticing topic), equity-culture-gender studies, and studies on mathematical problem posing, problem solving, modelling, STEM and STEAM education. The findings of this study may be useful in identifying current potential research areas in the field of mathematics education.